Implementasi Program Literasi Digital Untuk Penanggulangan Kenakalan Remaja di Nagari Panyakalan - Yana Maulidia Jusra; Isbandi Rukminto Adi (Metta : Jurnal Ilmu Multidisiplin, 2026)
This research implements the Stringer Action Research framework to address juvenile delinquency through digital literacy in Nagari Panyakalan. The research analyzes the implementation process, strategies, and dynamics of the digital literacy program, as well as identifies supporting and inhibiting factors during the Act stage. Using a qualitative approach with Stringer's cyclical method (Look, Think, Act), the study focuses on the Act stage. Data were collected through participatory observation, in-depth interviews, and focus group discussions. Findings indicate that the Action phase, realized through the "Sahabat Remaja Panyakalan" program and the "Saring Sebelum Sharing" workshop, was successfully implemented using participatory and adaptive strategies. Key supporting factors included youth enthusiasm, community leader support, and basic digital infrastructure. Challenges included limited facilities, disparities in digital literacy, and some parental resistance. The Act stage proved effective in enhancing digital literacy, fostering positive behavioral change, and reducing juvenile delinquency cases, underscoring the importance of well-executed action phases in community-based interventions.